2011
DOI: 10.1111/j.1365-2672.2011.05062.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of inorganic carrier-based formulations of fluorescent pseudomonads and Piriformospora indica on tomato plants and evaluation of their efficacy

Abstract: Aims:  Fluorescent pseudomonads are widely used as bioinoculants for improving plant growth and controlling phytopathogenic fungi. Piriformospora indica (Pi), a symbiotic root endophyte, also has beneficial effects on a number of plants. The present study focuses on the improvement of growth yields of tomato plants and control of Fusarium wilt using inorganic carrier‐based formulations of two fluorescent pseudomonad strains (R62 and R81) and Pi. Methods and Results:  The inorganic carrier‐based formulations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 35 publications
8
47
0
Order By: Relevance
“…Due to its closeness with AMF, Pi seems to have had a similar effect on growth of V. mungo plants in association with R62 and R81. The results obtained in the present study are in agreement with the results reported in a recent study by Sarma et al (2011) who investigated the effects of Pi and PGPR strains R62 and R81 on the growth of tomato plant, and also obtained the best results with the bio-inoculant formulation containing the consortium of Pi and R81.…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…Due to its closeness with AMF, Pi seems to have had a similar effect on growth of V. mungo plants in association with R62 and R81. The results obtained in the present study are in agreement with the results reported in a recent study by Sarma et al (2011) who investigated the effects of Pi and PGPR strains R62 and R81 on the growth of tomato plant, and also obtained the best results with the bio-inoculant formulation containing the consortium of Pi and R81.…”
Section: Discussionsupporting
confidence: 96%
“…The broth, containing additives, was mixed uniformly on a vortex mixer. Then inorganic carrier-based formulations of PGPR strains were prepared by mixing 20 ml of above mentioned broth with 80 g of sterilized carriers (Vidhyasekaran and Muthamilan 1995; Sarma et al 2011). The talcum powder-based formulations contained 2.5 9 10 10 and 6.3 9 10 10 cfu/g of R62 and R81 strains, respectively, whereas vermiculite-based formulations contained 3.0 9 10 10 and 2.4 9 10 10 cfu/g of R62 and R81 strains, respectively .…”
Section: Preparation Of Inorganic Carrier-based Formulationsmentioning
confidence: 99%
“…These high cell numbers could be beneficial for improving the productivity of agricultural crops. In a similar study, Sarma et al (2011) examined talcum and vermiculite based formulations of pseudomonas strains R62, R81 and Pi either in combinations or alone. They recorded a significant increases in growth and yield of tomato due to the application of (R81×Pi) talcum based formulation.…”
Section: Discussionmentioning
confidence: 99%
“…Talcum powder is used as an anti-sticking agent, an anti-caking agent, a carrier, a thickener, smooth filler and an adsorbent (EUROTALC 2017). Talcum powder was reported as a good carrier material for formulation of many bio-pesticides (Boyetchko et al, 1999;Brar et al, 2006;Sarma et al, 2011;Ritu et al, 2012;Tripathi et al, 2015;Private Pesticide Applicator Safety Education Mannual, 2015). …”
Section: Formulationmentioning
confidence: 99%